2019
DOI: 10.1097/scs.0000000000005653
|View full text |Cite
|
Sign up to set email alerts
|

Is Bilateral Sagittal Split Osteotomy of the Mandible With no Step Possible? A Modification in the Technique

Abstract: The mandibular ramus sagittal osteotomy is a usual procedure used to correct deformities of the lower third of the face. Modifications of the procedure will be presented to avoid the presence of palpable gap at mandibular body, easily seen in greater movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This cut extends from the mandibular angle to the lower end of the vertical buccal cortical osteotomy. Lower medial cortical osteotomies and a fourth horizontal osteotomy immediately above and parallel to the lower border were carried out by Mont’Alverne et al [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This cut extends from the mandibular angle to the lower end of the vertical buccal cortical osteotomy. Lower medial cortical osteotomies and a fourth horizontal osteotomy immediately above and parallel to the lower border were carried out by Mont’Alverne et al [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral sagittal split ramus osteotomy (BSSRO) is a technique of orthognathic surgery that is utilized to adjust excess, deficiency, and asymmetry of the mandible [1]. The sagittal split osteotomy was described by Trauner and Obwegeser and then modified by DalPont and Epker et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mont'Alverne et al in 2019 described an osteotomy similar to the design shown in this paper, however, specific indications, advantages and disadvantages for its use are not clarified [11]. The obtained preliminary results of this report can elucidate advantages of using this design such as the preservation of contact area for fixation between both segments, the protection of the vascular facial bundle in the ante-gonial notch by avoiding a cut on the lower border of the mandible, the preservation of the masseteric cinch insertion that cant be achieved by the angular osteotomy reported by Verweij et al [19], it reduces the need for implants or grafts in the gonial area for rounded faced patients, also eliminates the palpable step in the basilar and gonial outlines [11]. In addition, the step permits a better control of the position of the proximal segment limiting its auto-rotation.…”
Section: Discussionmentioning
confidence: 91%
“…1-3 ). Then a bicortical horizontal osteotomy is performed 5 to 8 mm above the basilar border of the mandibles angle, starting at the posterior border of the mandible in a posteroanterior direction to unify the osteotomies at the ante-gonial notch area where the previous cut was left [11]. The split is completed using osteotomes as conventional.…”
Section: Surgical Procedures and Technique Descriptionmentioning
confidence: 99%